농촌지역 중심의 행정구역 통합에 따른 경제적 효과 - 김_현중 (한국농촌경제연구원, 2011)
The purpose of the present study is to investigate the potential economic effects of consolidation of rural administrative districts even though municipal consolidation has been focused on urban areas in Korea. We utilize two methodologies to identify rural districts that can be consolidated. First, we identify rural districts suitable for the consolidation through cluster analyses. Second, we examine the economic effects of the consolidation based on a minimum cost approach. Following the methodologies, we identify four rural regions that are suitable for municipal consolidation. They are Yoenchoen- Dongduchoen, Gosung-Injae, Changnyeong-Uiryeng and Yangsan- Gijang. With respect to per capita expenditure savings projection, Gijang-Yangsan is expected to save the expenditure by 86% through the consolidation and 33% for Gosung-Injae, 23% for Yoenchoen-Dongduchoen and 21% was estimated for Changnyeong-Uiryeng. The results may cast important light on the necessity of consolidation in all four rural regions. While the present study entails limitations in data and empirical applications, it provides a theoretical basis and empirical implications for municipal consolidation in rural regions. The present study concludes with some policy implications and directions for future studies.
Keywords: 농촌지역; 행정구역 통합; 경제적 효과; 군집분석; 최소비용접근법; rural area; consolidation of administrative districts; economic effects; cluster analysis; minimum cost approach